Efforts to Increase the Success Rate of Artificial Insemination on Small Ruminant - Inounu, Ismeth (Indonesian Animal Sciences Society, 2014)
The success rate of artificial insemination (AI) technology in Indonesia is still low, especially on small ruminants. At experimental station condition, it was reported that the success rate of intrauterine AI was high (78.9% lambing percentage), while intracervix AI technique was still low (47.6% lambing percentage). Various things that could affect the success rate of AI program are discussed in this paper. Efforts to improve the success of artificial insemination in small ruminants (goats and sheep) can be done through the selection of productive female with good reproductive cycle, accurate dose of hormonal synchronization, followed by proper estrous detection and semen placement at the right time. Each stage is still open for more detailed study in order to obtain satisfactory results. Key words: Artificial insemination, small ruminant, success rate